2020
DOI: 10.1364/oe.379960
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cascade laser-pumped terahertz molecular lasers: frequency noise and phase-locking using a 1560 nm frequency comb

Abstract: The recent demonstration of a terahertz (THz) molecular gas laser pumped by a mid-infrared quantum cascade laser (QCL) has opened up new perspectives for this family of sources, traditionally relying on CO2-laser pumping. A so far open question concerning QCL-pumped THz molecular lasers (MLs) is related to their spectral purity. Indeed, assessing their frequency/phase noise is crucial for a number of applications potentially exploiting these sources as local oscillators. Here this question is addressed by repo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In that limit, the only variation in PTHz from line to line and molecule to molecule comes from the terms nTHz, nIR, and Pth. Even if such an approximation is acceptable for operating a QPML over a narrow range of frequencies and pressures, as was done in previous work [2,5], it is not valid for estimating how the widely tunable QPML performance varies from molecule-to molecule and from line-to-line. Moreover, the approximation proposed in [4] requires that the pressure and/or cavity length be varied to achieve the 𝛼 => 𝐿 > 1 condition.…”
mentioning
confidence: 93%
“…In that limit, the only variation in PTHz from line to line and molecule to molecule comes from the terms nTHz, nIR, and Pth. Even if such an approximation is acceptable for operating a QPML over a narrow range of frequencies and pressures, as was done in previous work [2,5], it is not valid for estimating how the widely tunable QPML performance varies from molecule-to molecule and from line-to-line. Moreover, the approximation proposed in [4] requires that the pressure and/or cavity length be varied to achieve the 𝛼 => 𝐿 > 1 condition.…”
mentioning
confidence: 93%
“…Unlike electronic sources, the Manley-Rowe effect in these QCLpumped molecular lasers (QPMLs) causes the power to increase with increasing frequency. Consequently, reports of power exceeding 1 mW [13] and tunability approaching 1 THz [12] from QPMLs foreshadow the potential of these sources to span the terahertz gap.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of ongoing research topics, e.g., high-speed photonic analogto-digital conversion [140], dual-comb spectroscopic measurements [141][142][143][144][145][146][147], X-band ultra-low-noise microwave generation [148][149][150][151], and astro-combs [152][153][154][155], require frequency combs with large mode spacing, therefore novel optical frequency combs aim to boost the comb spacing over the GHz level. Representative techniques generating high-repetition-rate laser sources are QCL-based combs [156,157], microcombs [158][159][160], and EO-modulated combs [161,162]. The detailed study of noise behavior in these novel combs could be found in this literature [150,[162][163][164][165].…”
Section: Discussionmentioning
confidence: 99%